No moderating effect of coping skills on the association between bullying experience and self-esteem: Results from K-CHILD study - Saimon, Yukino; Doi, Satomi; Fujiwara, Takeo (Frontiers in Psychology, 2022)
Few studies have investigated the moderating effect of coping skills on the association between bullying experience and low self-esteem. The aim of this study is to examine whether coping skills have a moderating effect on the association between bullying experience and self-esteem among Japanese students. Data from the population-based Kochi Child Health Impact of Living Difficulty (K-CHILD) study conducted in 2016 were analyzed. Participants included fifth- and eighth-grade students living in Kochi Prefecture, Japan. A questionnaire for the students (n=5,991) assessed the bullying experience, self-esteem (the Japanese Edition of the Harter's Perceived Competence Scale for Children), and coping skills which comprised six types (The shortened version of coping skills for elementary school children). Multivariate linear regression analyses were conducted to examine the association between bullying experience and self-esteem, and then the moderating effects of six types of coping as interaction terms on the association were considered. Bullying experience was inversely associated with self-esteem. All six types of coping did not moderate the relationship between bullying experience and low self-esteem even after adjusting for cofounders (all p for interaction >0.15). Coping skills did not moderate the association between bullying experience and self-esteem, suggesting that intervention to boost coping skills to mitigate the adverse effect of bullying experience may not be promising.